Effect of local leg cooling on upper limb trajectories and muscle function and whole body dynamic balance - Piedrahita, H.; Oksa, J.; Rintamäki, H.; Malm, C. (European Journal of Applied Physiology, 2009)
This study was designed to find out if local leg cooling affects muscle function and trajectories of the upper limb during repetitive light work as well as capability to maintain dynamic balance. Nine healthy female subjects performed repetitive lifting task with right hand for 60 min while standing in front of a table with six target angles (30°-220°) and with the legs inside a container with 15°C cold water (Cold condition, C) or without water (Normal condition, N). Muscle temperature of the medial aspect of the gastrocnemius, rectal, and skin temperatures were measured continuously. The trajectories of the right upper limb were recorded with a 3D motion analysis system. Muscular strain (averaged EMG, a-EMG) and EMG gaps in eight muscles of the right upper limb were measured. End point excursion depicting the ability to maintain dynamic balance was measured before and after each experiment. Leg cooling decreased significantly (P < 0.05) the muscle and the mean skin temperature in C compared with N (6.7 and 2.2°C, respectively). No marked changes in the trajectories or EMG activity were observed between the different environmental conditions. The end point excursion was significantly (P < 0.05) reduced in C compared with N and a positive correlation between excursion and muscle temperature was found at the end of the working period in C. In conclusion, local leg cooling did not affect upper limb muscle function or trajectories, but ability to maintain dynamic balance was reduced.